Pengaruh Lama Fermentasi terhadap Karakteristik Kimia, Organoleptik dan Total Plate Count (TPC) Cumi Kering (Loligo sp.): Effects of Fermentation Time on Chemical, Organoleptic Characteristics and Total Plate Count of Dried Squid (Loligo sp.) - Agustiana, Agustiana; Adawyah, Rabiatul; Syifa, Muhammad; Habibie, Rifqi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
This study aimed to determine the effects of fermentation time on chemical, organoleptic characteristics and total plate count of dried squid (Loligo sp.) product. This study used 3 treatments of fermentation time namely treatment O (1 day of fermentation), treatment A (3 days of fermentation) and treatment B (5 days of fermentation). The results showed that fermentation time significantly affected the chemical characteristics of dry squid. The highest protein content was observed in treatment O (40.38±0.92%) and the lowest water content was in treatment O ( 12.49±1.17%) while the lowest pH level was in treatment A (6.01±0.01). The organoleptic characteristics including appearance, aroma, taste and texture were more preferred in treatment A than in other treatments. The lowest total plate count in treatment B was 5.84±1.3 log10 CFU/mL.